Ly49 Receptors: Innate and Adaptive Immune Paradigms - Rahim, Mir Munir A.; Tu, Megan M.; Mahmoud, Ahmad B.; Wight, Andrew; Abou-Samra, Elias; Lima, Patricia D.; Makrigiannis, Andrew P. (Frontiers in Immunology, 2014)
The Ly49 receptors are type II C-type lectin-like membrane glycoproteins encoded by a family of highly polymorphic and polygenic genes within the mouse natural killer gene complex (NKC). This gene family is designated Klra, and includes genes that encode both inhibitory and activating Ly49 receptors in mice. Ly49 receptors recognize class I major histocompatibility complex (MHC-I) and MHC-I-like proteins on normal as well as altered cells. Their functional homologs in humans are the killer cell immunoglobulin-like receptors (KIRs), which recognize HLA class I molecules as ligands. Classically, Ly49 receptors are described as being expressed on both the developing and mature natural killer (NK) cells. The inhibitory Ly49 receptors are involved in NK cell education, a process in which NK cells acquire function and tolerance towards cells that express ‘self-MHC-I’. On the other hand, the activating Ly49 receptors recognize altered cells expressing activating ligands. New evidence shows a broader Ly49 expression pattern on both innate and adaptive immune cells. Ly49 receptors have been described on multiple NK cell subsets, such as uterine NK (uNK) and memory NK cells, as well as NKT cells, dendritic cells (DC), plasmacytoid dendritic cells (pDC), macrophages, neutrophils and cells of the adaptive immune system, such as activated T cells and regulatory CD8+ T cells. In this review we discuss the expression pattern and proposed functions of Ly49 receptors on various immune cells and their contribution to immunity.